Analisis Profil Bawah Permukaan Pantai Lumpue Kota Parepare - Sirajuddin, Haerany; Maulidani, Sri (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2019)
Lumpue Beach Subsurface Profile Analysis of Parepare City. This study aims to analyze the subsurface profile of Lumpue beach which is directly contaminated with activities around the coast. In this study, the Wenner Schlumberger method was used in the Lumpue beach area, Perepare City, South Sulawesi Province. The tool used is a multichannel geoelectric with a maximum length of 480 m in each trajectory, in this study there are 3 trajectories in which the first trajectory is 480 m with depth as deep as 91.2 m and the resistivity results obtained range from 0.207 -> 97.8 Î©m which identified as alluvium containing clay soil, silt soil, sandstone and pyroclastic rock bolder that has been contaminated by sea water. At lane 2 intersects the middle lane 1 with a length of 240 m and identified depths of 91.2 m, the recorded resistivity results range between 5.52 -> 623 Î©m where the resistivity value identifies the alluvium material, which contains clay, silt soil , sandstone that has been contaminated with water and the presence of some pyroclastic rock inserts that are contaminated by water. Whereas lane 3 intersects lane 1 at the end with a lenght of 240m and a depth of 91.2 m, while the recorded resistivity results range from 0.354 - 11776 Î©m where from the recorded resistivity results the material contained in lane 3 is the inserted alluvium material. by pyroclastic rocks. The area covered by the track is an area with alluvium material which is an alluvial unit and most of it is contaminated by water, either by sea water or fresh groundwater and is inserted by pyroclastic rocks.